Short term water heat storage : studies of velocity and temperature fields and their importance for sizing of the storage - Dahl, Jan (Luleå tekniska universitet, Energivetenskap, 1993)
Short term water heat storage's have been introduced in many district heating systems. The main reason for this is the possibilities opened by the storage for optimization of the generation of heat and electricity in combined heat and power plants. The basic task for the storage is then to bridge the timevise gap between the heat demand and supply of heat from a cogeneration plant. Water heat storage's can also be useful in district heating systems supplied with industrial waste heat. The water volume in the storage must be stratified to avoid degradation of the quality of the heat that has been charged. Experimental studies of phenomena that influence the stratification and cause a degradation of the quality has been made in model storage's of different sizes The studies include extensive temperature measurements and velocity measurements with different techniques. Laser Doppler Anemometry was used to measure the vertical velocities in the boundary layer at the outer walls. The gradient zone was found to have a strong impact on the velocity field. The maximum velocity in the boundary layer was increasing due to available height up to a certain level where it remained constant. Particle Image Velocimetry Technique were used for measuring the two dimensional velocity field in seeded water in a plane illuminated by a laser. These measurements showed that large scaled convection cells appeared both above and below the gradient zone. The exchange of water between the boundary layer and the core was also shown in these experiments. A video based PIV-technique was developed where a complete charging experiment could be recorded on a video tape. The pictures were analysed in an image processing program which made it possible to evaluate the whole velocity field. On basis of simulations for a case study representing the district heating system in Piteå it was found that heat quality degradation is not essential for the optimization of the storage volume. The different phenomena that influence the quality degradation are ...